Effectiveness of Crossword Puzzle Learning Media to Improve Arabic Vocabulary in Maahad Attarbiyah Lilulumidiyah Teras City: Efektivitas Media Pembelajaran Crossword Puzzle untuk Meningkatkan Kosa Kata Bahasa Arab di Maahad Attarbiyah Lilulumidiyah Kota Teras - Husna Kadasae; Najih Anwar, S.Ag, M.Pd (Universitas Muhammadiyah Sidoarjo, 2022)
This research focuses on Arabic language teaching to Grade VII Mutawassitah students at Maahad Attarbiyah Lilulumidiniyah High School. The study identifies the main obstacle for students as the lack of vocabulary knowledge, attributed to the use of general and uninspiring learning media such as PowerPoint and picture cards. To address this, an innovative learning media approach using crossword puzzles was implemented through classroom action research (CAR). Data collection involved written tests, observations, and practical assessments, analyzed using a simple formula. The initial observation revealed low scores and student engagement, prompting the adoption of crossword puzzles in collaboration with Arabic language teachers. The first cycle demonstrated a 40% improvement in post-test scores, leading to further adjustments and planning for the second cycle. Notably, the second cycle showed a significant increase, reaching a 100% post-test observation score. The findings highlight the effectiveness of crossword puzzle learning media in enhancing vocabulary understanding among Arabic language learners. Highlights: Lack of vocabulary knowledge: The research identifies the main obstacle faced by Grade VII Mutawassitah students at Maahad Attarbiyah Lilulumidiniyah High School in learning Arabic language is the insufficient grasp of vocabulary. Innovative learning media: The study emphasizes the need for innovative learning media to enhance students' understanding of Arabic vocabulary, as traditional methods such as PowerPoint and picture cards have been found to be ineffective and monotonous. Crossword puzzles in classroom action research: The research employs crossword puzzles as a novel approach within the framework of classroom action research (CAR). The implementation of crossword puzzles shows promising results in improving students' vocabulary acquisition and engagement in Arabic language learning. Keywords: Arabic language teaching, vocabulary knowledge, innovative learning media, classroom action research, crossword puzzles